Effectiveness of Gamma Irradiation for Decontamination of Microbes on Tea Parasite Herb Scurrula atropurpurea (Bl.) Dans - E. Katrin; M. Yulianti; H. Winarno (PPIKSN-BATAN, 2011)
The purpose of this study was to find the minimum and maximum dose of gamma irradiation on dried tea parasite herb that can reduce the number of microbes without reducing the inhibitory activity against leukemia L1210 cells. Samples of tea parasite herbs were irradiated by gamma rays with doses of 0, 5, 7.5, 10, 15 and 20 kGy. The microbial contamination, cytotoxic activities and the chromatogram profiles of irradiated and unirradiated samples were observed. The results revealed that the bacteria contaminants of 7.57 x 109 cfu/g were eliminated after irradiation of the samples with dose of > 7.5 kGy, meanwhile the mold-yeast contaminants of 5.68 x 108 cfu/g were eliminated after irradiation of the samples with dose of > 5 kGy. Ethyl acetate extracts of irradiated samples until the dose of 10 kGy were still able to maintain its cytotoxic activity against L1210 leukemia cells proliferation with IC50 values of < 30 µg/ml. Fractionation of ethyl acetate extracts of each sample by open column chromatograph was obtained four fractions from each extract. Among the fractions, fraction 2 was the most active fraction which had a potent as anticancer agent. Cytotoxic activities assay of fraction 2’s showed that this fractions significantly decreased after irradiation of samples with doses up to 10 kGy. The thin layer chromatogram profiles of fraction 2 from irradiated and unirradiated samples showed that spot 2 and 3 gradually tended to fade. It is suggested that 7.5 and 10 kGy were the minimum and maximum irradiation dose for bacterial and mold/yeast decontamination with the initial contamination of 7.57 x 109 cfu/g and 5.68 x 108 cfu/g respectively. At this condition, the bacteria and mold/yeast have been killed, whereas the cytotoxic activities of active components (ethyl acetate extract and fraction 2) in tea parasite herbs decreased, but the decrease was not significant and did not remove these cytotoxic activities.Received: 20 November 2010; Revised: 07 September 2011; Accepted: 19 September 2011